Persepsi Akuntan dan Mahasiswa terhadap Etika Penyusunan Laporan Keuangan - Yana Yuliana; Anita Wijayanti; Yuli Chomsatu (Universitas Jember, 2016)
The financial report is an important element for the company to make decision. Presentation of financial statements must appropriate with the ethics that supposed, so that it can minimize levels of cheating both individuals and corporations. The purpose of this study was to determine students' perceptions of accountants and ethical preparation of financial statements covering disclosure, cost and benefit, responsibility, and misstate. The population in this study are all accountants who are in Klaten and Surakarta was for students are enrolled in private and state as a 7th semester student or have been through the course of business and professional ethics. The sample used was 100 accountants and 100 accounting students. Data collected by spreading questionnaire to all respondents. Measurement scale used is Likert scale. This study uses a hypothesis test Independent sample t test. The results of this study indicate that there are differences in the perception of accountants and accounting students to the ethical preparation of financial statements which includes the disclosure and responsibility. And there are differences in perceptions of ethical financial statements include cost and benefit and misstate. Keywords: Perception, ethics, financial report